2018
DOI: 10.3390/ijerph15071390
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Particulate Matter and Volatile Organic Compound Emissions from the Combustion of Waste Vinyl

Abstract: Vinyl samples were burned in a controlled environment to determine the characteristics of particulate matter (PM) and volatile organic compound (VOC) emissions during the combustion process. Open burning of plastic or vinyl products poses several environmental and health risks in developed and developing countries, due to the release of high concentrations of harmful pollutants. The production of fine and ultrafine particles was significant. At a heat flux of 25 kW/m2, the production of PM of 0.35 μm in size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Therefore, 0.45 µm had the highest peak concentration among all the compounds. The study demonstrated that the smallest-sized particles (0.35 and 0.45 µm), which represents the most hazardous for the population health, constituted the greatest percentage of total PM emissions, founding that the concentration of ultrafine particles represent another source of hazard for population health [77]. The review of the scientific literature indicated that open burning should be avoided and replaced with appropriate and sustainable technologies for reducing environmental pollution and public concerns.…”
Section: Environmental and Social Issues Due To Sw Mismanagementmentioning
confidence: 99%
“…Therefore, 0.45 µm had the highest peak concentration among all the compounds. The study demonstrated that the smallest-sized particles (0.35 and 0.45 µm), which represents the most hazardous for the population health, constituted the greatest percentage of total PM emissions, founding that the concentration of ultrafine particles represent another source of hazard for population health [77]. The review of the scientific literature indicated that open burning should be avoided and replaced with appropriate and sustainable technologies for reducing environmental pollution and public concerns.…”
Section: Environmental and Social Issues Due To Sw Mismanagementmentioning
confidence: 99%
“…Due to a tighter and earlier emission reduction policy, the VOC trend in Los Angeles decreased earlier than in London [45]. However, VOCs are still detectable in heavily industrialized countries with petrochemicals and heavy-traffic cities, or areas of open waste-burning or combustion of hazardous waste [49]. This study demonstrated that acrolein exceeded ambient air quality standards to the greatest degree.…”
Section: Comparison With Other Studies Performed In Other Continentsmentioning
confidence: 76%
“…Furthermore, since carbon is a significant building block of plastic, simple incineration is a source of greenhouse gas emissions and potentially other hazardous substances (Barabad et al, 2018). Overall, the use of virgin plastic results in two different streams of CO 2 emissions.…”
Section: Plastic Recycling: Challenges and Opportunitiesmentioning
confidence: 99%